Revealing Smallholder Farmers’ Perceptions on Sustainable Intensification in Malawi - Meijer, Sanderijn; Cossu, Alessandra; Abera, Wuletawu; Tamene, Lulseged D.; Mponela, Powell; López Ridaura, Santiago; Timler, Carl; Groot, Jeroen C.J. (International Maize and Wheat Improvement Center, 2023)
Malawi, with a population density of around 20 million people, has 85% of its inhabitants living in rural areas, primarily depending on agriculture for their livelihoods (World Bank, 2022). The predominant cultivation of maize, a key staple crop, plays a role in soil degradation and nutrient exhaustion (Thierfelder et al., 2013). Smallholder farmers, who typically possess less than one hectare of land, encounter challenges in both accessing and affording inorganic fertilizers (Duchoslav & Rusike, 2021).